2008
DOI: 10.1007/s10508-007-9302-0
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Hormonal Contraception on Mood and Sexual Interest among Adolescents

Abstract: Mood and sexual interest changes are commonly cited reasons for discontinuing hormonal contraceptives. Data, however, are inconsistent and limited to adult users. We examined associations of hormonal contraceptive use with mood and sexual interest among adolescents. We recruited 14-17 year old women primary care clinics and followed them longitudinally for up to 41 months. Participants completed face-to-face interviews quarterly and two 12 week periods of daily diary collection per year. On daily diaries, part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 28 publications
2
34
0
1
Order By: Relevance
“…The discrepancy in findings between adult women and adolescent girls might be related to the duration period of OC use and the time to adjust to the effects of OC intake. Longitudinal research is needed to elucidate the effects of oral contraceptive use on HPA-axis functioning in adolescence, since especially longterm effects of OC use are still unknown (Ott et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy in findings between adult women and adolescent girls might be related to the duration period of OC use and the time to adjust to the effects of OC intake. Longitudinal research is needed to elucidate the effects of oral contraceptive use on HPA-axis functioning in adolescence, since especially longterm effects of OC use are still unknown (Ott et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…4 Although much larger, Urdl's study did not include adolescents younger than 18 years, did not measure baseline mood, and did not use a validated tool to measure mood, limitations shared by other studies which have reported on mood in patch users. 5,24,42 Given the frequency with which women attribute mood changes to hormonal contraception, 43 this remains an area where significant further study is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Neither weight gain nor mood changes have been reliably linked to use of combined hormonal contraception. [118][119][120] Recommendations for managing adverse effects have been published elsewhere 121 or can be found online (http:// www.managingcontraception.com/qa/ index.php). COCs have few contraindications in healthy female adolescents.…”
Section: Coc Prescribingmentioning
confidence: 99%